2019
DOI: 10.1099/jgv.0.001321
|View full text |Cite
|
Sign up to set email alerts
|

Identification of peptide domains involved in the subcellular localization of the feline coronavirus 3b protein

Abstract: Feline coronavirus (FCoV) has been identified as the aetiological agent of feline infectious peritonitis (FIP), a highly fatal systemic disease in cats. FCoV open reading frame 3 (ORF3) encodes accessory proteins 3a, 3b and 3 c. The FCoV 3b accessory protein consists of 72 amino acid residues and localizes to nucleoli and mitochondria. The present work focused on peptide domains within FCoV 3b that drive its intracellular trafficking. Transfection of different cell types with FCoV 3b fused to enhanced green fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…MPP cleavage occurs in the mitochondrial matrix and is required to cleave the N terminal mitochondrial signal sequence before a protein can enter inside. There are reports on other corona viruses where experiments have shown that the viral proteins showing mitochondrial localization possess TOM20 recognition motifs in the N terminal region [6]. Hence, these factors are important to consider while assessing the localization of any viral protein in mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…MPP cleavage occurs in the mitochondrial matrix and is required to cleave the N terminal mitochondrial signal sequence before a protein can enter inside. There are reports on other corona viruses where experiments have shown that the viral proteins showing mitochondrial localization possess TOM20 recognition motifs in the N terminal region [6]. Hence, these factors are important to consider while assessing the localization of any viral protein in mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…These infections often serve as useful models of human and animal disease. MHV represents a spectrum of coronaviruses with tropisms for a wide variety of mouse cells or tissues, such as the enteric epithelium, respiratory epithelium, vascular endothelium, lymphoid tissue, hemopoietic tissue, liver and central nervous system [ 4 , 5 , 8 ].…”
Section: Animal Coronavirusesmentioning
confidence: 99%